2008
DOI: 10.1111/j.1469-0691.2008.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic background of Escherichia coli isolates from patients with spontaneous bacterial peritonitis: relationship with host factors and prognosis

Abstract: Spontaneous bacterial peritonitis (SBP) is a severe complication in patients with cirrhosis and ascites. It is predominantly caused by Escherichia coli. The phylogenetic group and virulence genotype of E. coli isolates causing SBP were investigated, and the association of these characteristics with host factors and prognosis was examined. Seventy-six episodes of E. coli SBP that occurred over a 9-year period were studied. The phylogenetic group of the isolates and the presence of 36 virulence factor genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
1
16
2
Order By: Relevance
“…Previous investigations showed that FQ r isolates are associated with lower VF prevalences than FQ s isolates. An exception was for iutA, which was universally detected at a higher frequency in FQ r isolates (2,27,38,41,42,47). Although we found that more FQ r isolates belonged to phylogenetic group B2, they were proportionally less prevalent in this group than in group D. Previous studies of these particular relationships have produced conflicting results (2,27,38).…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Previous investigations showed that FQ r isolates are associated with lower VF prevalences than FQ s isolates. An exception was for iutA, which was universally detected at a higher frequency in FQ r isolates (2,27,38,41,42,47). Although we found that more FQ r isolates belonged to phylogenetic group B2, they were proportionally less prevalent in this group than in group D. Previous studies of these particular relationships have produced conflicting results (2,27,38).…”
Section: Discussioncontrasting
confidence: 54%
“…The majority of isolates belonged to phylogenetic groups B2 and D. While similar observations have been made with ExPEC strains originating from patients with bacteremia (26, 36, 42, 46), the urinary tract (24,25,35,41,43), both of these (4, 22, 37), or different sources (2,20,27), others have reported that ExPEC strains from the urinary tract and patients with bacteremia fall predominantly into phylogenetic groups A (15) and D (34), respectively. The study design and the number and source of the isolates, along with demographic and epidemio- logic factors relating to the patient population, probably account for these discordant results.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Although prophylaxis with norfloxacin is recommended in patients at high risk of infection, this may promote the emergence of fluoroquinolone-resistant organisms (3,29). Screening patients for the presence of translocating isolates in the gut could help identify those who would benefit the most from norfloxacin prophylaxis.…”
Section: Vol 48 2010mentioning
confidence: 99%
“…1,2 Phylogenetic analyses have shown that E. coli strains are located in 4 main phylogenetic groups (A, B1, B2, and D) and the strains differ in phenotypic characteristics including antibioticresistance patterns, and resistance to special antibiotics can be related to particular phylogenetic groups. [3][4][5][6] The World Health Organization (WHO) reported that approximately 50% of the universally produced antibiotics are consumed for veterinary usages such as prophylactic and growth promotion purposes. [7][8][9] The increase of antibiotic resistance following the use of antibiotics such as beta-lactams and growing the commensal and pathogenic ESBL (extended-spectrum beta-lactamase)-producing bacteria like E. coli strains especially in foodproducing animals pose a threat to the public health and food safety.…”
Section: Introductionmentioning
confidence: 99%